Police Officer Attitudes Toward Muslims and Islam: “Worlds Apart”? - Keeling, Deborah G. (American journal of criminal justice, 2011)
American Muslims may be the most diverse group of Muslims in any country in the world. There are an estimated 5–7 million Muslims in the United States. They represent a number of different nationalities, ethnicities, and interpretations of Islam. Moreover, over the past few years there appears to be an increase in the immigration of Muslims to the United States. Law enforcement agencies are currently concerned with the danger of “homegrown” terrorists and terrorism in the U.S. American Muslims likely represent the best source of information regarding those who have been dangerously radicalized within their various communities. To cull important information from the community, police agencies need to contact and communicate with their Muslim population. The ability to achieve these goals would seem to be shaped by both organizational and individual officer understanding and perception of both Muslims and Islam. Organizations and officers with accurate views would likely find efforts at communication and information exchange more fruitful. The current research seeks to assess the knowledge of and attitudes toward Muslims and Islam among our sample of American police officers. Four general areas will be explored in the survey. First, we examine the respondents’ general understanding of many of the basic tenets of Islam. Next, we wish to explore some of the respondents’ attitudes regarding Muslims and Islam. Third, we explore the respondents’ perception of media treatment of Muslims and Islam. Last, the level of officer contact with Muslims is examined.